Art for art's sake? The influence of art framing and context on the evaluation of immoral behaviour - Goetz, Itay; Bernhardt, Lara; Karg, Friederike Margareta; Pastukhov, Alexander (Sasha); Carbon, Claus-Christian (Frontiers in Communication, 2025)
Artists often challenge societal norms through their artworks; hence, red lines have notoriously been crossed throughout art history. This is particularly the case since the Renaissance, when artists were emancipated from craftspeople and began challenging beholders regarding visual habits, religious, and ethical norms. Because artworks possess a special status in our society, they are processed qualitatively differently from everyday life objects. Hence, they offer the opportunity for dialogue, disentangled from automatic evaluative heuristics and strict categories. We tested how labeling visual depictions of immoral acts as art vs. non-art affects the overall evaluation of such depictions. Furthermore, we explored the impact of presenting pictures in a physical art gallery on such evaluations. Participants (N = 140) were allocated into one of three viewing conditions: art-gallery, art-online, and non-art-online, where the same set of 20 pictures was presented. The pictures evoked similar adverse emotional reactions when shown as art and non-art, including in the gallery. Nevertheless, regarding beauty, interest and happiness rates, the pictures were evaluated higher when labeled art and even higher when presented in the gallery. Additionally, participants reported lower understanding rates and higher surprise rates for the art-labeled pictures, perhaps indicating that people were less likely to immediately apply standard heuristics and categorization routines when processing them. We conclude that art, especially when presented in typical art contexts, provides special conditions that invite beholders to challenge, adapt, and extend their habits. Art may offer a unique context for engaging with extreme or novel ideas, inviting reflection and even transformation.